Impact of Content Writing in Purchase Decision Process in the Software Industry - Khan, Sadab Sifer-E-Murshed (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.